Neutrophil‐Lymphocyte Ratio Is a Prognostic Marker in Patients with Locally Advanced (Stage IIIA and IIIB) Non‐Small Cell Lung Cancer Treated with Combined Modality Therapy. (June 2017) - Scilla, Katherine A.; Bentzen, Søren M.; Lam, Vincent K.; Mohindra, Pranshu; Nichols, Elizabeth M.; Vyfhuis, Melissa A.; Bhooshan, Neha; Feigenberg, Steven J.; Edelman, Martin J.; Feliciano, Josephine L.
Abstract: Background: Neutrophil‐lymphocyte ratio (NLR) is a measure of systemic inflammation that appears prognostic in localized and advanced non‐small cell lung cancer (NSCLC). Increased systemic inflammation portends a poorer prognosis in cancer patients. We hypothesized that low NLR at diagnosis is associated with improved overall survival (OS) in locally advanced NSCLC (LANSCLC) patients. Patients and Methods: Records from 276 patients with stage IIIA and IIIB NSCLC treated with definitive chemoradiation with or without surgery between 2000 and 2010 with adequate data were retrospectively reviewed. Baseline demographic data and pretreatment peripheral blood absolute neutrophil and lymphocyte counts were collected. Patients were grouped into quartiles based on NLR. OS was estimated using the Kaplan‐Meier method. The log‐rank test was used to compare mortality between groups. A linear test‐for‐trend was used for the NLR quartile groups. The Cox proportional hazards model was used for multivariable analysis. Results: The NLR was prognostic for OS ( p  < .0001). Median survival in months (95% confidence interval) for the first, second, third, and fourth quartile groups of the population distribution of NLR were 27 (19–36), 28 (22–34), 22 (12–31), and 10 (8–12), respectively. NLR remained prognostic for OS after adjusting for race, sex, stage, performance status, and chemoradiotherapy approach ( p  = .004). Conclusion: To our knowledge, our series is the largest to demonstrate that baseline NLR is a significant prognostic indicator in LANSCLC patients who received definitive chemoradiation with or without surgery. As an indicator of inflammatory response, it should be explored as a potential predictive marker in the context of immunotherapy and radiation therapy. Implications for Practice: Neutrophil‐lymphocyte ratio measured at the time of diagnosis was associated with improved overall survival in 276 patients with stage IIIA and IIIB non‐small cell lung cancer (NSCLC) treated with definitive chemoradiation with or without surgery. To our knowledge, our series is the largest to demonstrate that baseline neutrophil‐lymphocyte ratio is a significant prognostic indicator in locally advanced NSCLC patients who received definitive chemoradiation with or without surgery. Neutrophil‐lymphocyte ratio is an inexpensive biomarker that may be easily utilized by clinicians at the time of locally advanced NSCLC diagnosis to help predict life expectancy. Abstract : Neutrophil‐lymphocyte ratio is a measure of systemic inflammation that appears prognostic in localized and advanced non‐small cell lung cancer. Increased systemic inflammation portends a poorer prognosis in cancer patients. This study explores whether low neutrophil‐lymphocyte ratio at diagnosis is associated with improved overall survival in patients with locally advanced non‐small cell lung cancer.